Monitoring ammonia concentrations in more than 10 stations in the Po Valley for the period 2007–2022 in relation to the evolution of different sources - Colombi, C.; D’Angelo, L.; Biffi, B.; Cuccia, E.; Dal Santo, U.; Lanzani, G. (Frontiers in Environmental Health, 2024)
Regarding secondary aerosols, in addition to the significant contribution of anthropogenic gases such as NOx and SO2, atmospheric ammonia (NH3) plays a crucial role as the primary basic gaseous species capable of neutralizing acidic compounds. This acid–base reaction is responsible for the formation of ammonium nitrate (NH4NO3), constituting up to 60% of PM10 within the Po River basin in Italy. Ion chromatographic analyses performed on offline samples indicate that this secondary inorganic species exhibits minimal concentration variability over the Po Valley because of limited air circulation due to orography and mesoscale air circulation. Therefore, investigating gaseous precursors becomes crucial. From the northern to the southern part of Lombardy—the region at the center of the basin—NH3 emission amounts account for 2.5, 11.1, and 27.7 t/y/km2, mainly due to agriculture and livestock activities (∼97%). To study NH3 temporal and spatial variability, the Environmental Protection Agency of Lombardy Region has been monitoring NH3 concentrations across its territory since 2007, with 10 active monitoring sites. Annual and seasonal cycles are presented, along with a focus on different stations, including urban, low-mountain background, high-impact livestock, and rural background, highlighting the impact of various sources. Measurements indicate that within the Po basin, NH3 concentrations can reach up to 700 µg/m3 (as an hourly average) in proximity to the main gaseous NH3 source. Instrument intercomparisons among online monitors and passive vials, as well as different online monitors, are presented. Therefore, this paper provides crucial data to understand the formation of secondary inorganic aerosols in one of the most important hotspot sites for air pollution.